Approaching Ecological Sustainability in the Emerging Insects-as-Food Industry. (February 2019) - Berggren, Åsa; Jansson, Anna; Low, Matthew
Abstract : The emerging insects-as-food industry is increasingly promoted as a sustainable alternative to other animal protein production systems. However, the exact nature of its environmental benefits are uncertain because of the overwhelming lack of knowledge concerning almost every aspect of production: from suitable species, their housing and feed requirements, and potential for accidental release. If ecological sustainability is to be a hallmark of mass insect rearing for consumption, ecologists need to engage in research related to sustainability criteria that are directly linked to key elements of the development of the industry. There is more to this subject than simply comparing feed-conversion ratios (FCRs) of insects to traditional livestock production, and we highlight areas where research needs to be immediately focused. Highlights: Insects-as-food is an emerging industry in Western countries as a solution to increased animal protein demand. Environmental sustainability is a key justification for its development; however, a lack of basic research on almost all aspects of production means the future environmental impact of the mass rearing of insects is largely unknown. Sustainability will be mostly determined by the insect species reared, type of feed used, waste utilisation and management, facility design, and geographic location – as these will heavily influence the amount and quality of protein produced per resource unit input and waste output. We outline where ecologists and animal scientists need to urgently focus their research efforts related to key criteria of the insects-as-food industry to ensure its development is in line with long-term ecological sustainability.